A Rare Case of Mycosis Fungoides in the Oral Cavity and Small Intestine Complicated by Perforation - Drew Arthur Emge; Juri Bassuner; Daniel J. Lewis; Madeleine Duvic (Karger Publishers, 2016)
Extracutaneous involvement in mycosis fungoides (MF) carries a poor prognosis. Oral and gastrointestinal (GI) tract lesions are both rare locations of disease. We describe the clinical findings of one case with oral and GI MF complicated by perforation after systemic antineoplastic treatment, and review the relevant literature. The patient had a 1-year history of MF before development of tongue and palate tumors. He was treated with local electron beam radiation, but re-presented to the hospital after what was found to be small intestine perforation following systemic antineoplastic therapy. The case reveals key insights into the progression and complications of lymphomas with GI tract involvement.